ChemInform Abstract: Modular Prolinol Chiral Ligands for Enantioselective Addition of Diethylzinc to Aromatic Aldehydes. Issue 29 (1st July 2013) - Gou, Shaohua; Ye, Zhongbin; Feng, Mingming; Jiang, Wenchao
Abstract A wide range of aromatic aldehydes with electron‐donating and ‐withdrawing substituents are transformed into the corresponding alcohols under mild conditions.